Proactive spatial planning in regard to a new regional mobility hub. The case of Ebreichsdorf. - Dillinger, Thomas; Neuhaus, Markus (My University, 2018)
"Smart City Ebreichsdorf" ist ein vom Klima- und Energiefonds gefördertes Forschungsprojekt unter der Leitung der TU Wien zusammen mit der Stadtgemeinde Ebreichsdorf, dem Energiepark Bruck/Leitha und der Niederösterreichischen Energie- und Umweltagentur Betriebs-GmbH. Ziel ist es, einen Nachdenkprozess zur smarten Entwicklung der Stadtgemeinde Ebreichsdorf anzustoßen. Ein Schwerpunkt dabei ist die proaktive Verkehrsplanung mit der Schaffung einer neuen Eisenbahnstrecke samt Bahnhof in Pendlerdistanz zu Wien. Weitere Schwerpunkte sind: Minimierung der Bodenversiegelung, Übernahme neuer Technologien für die Mobilität der Zukunft, Verhinderung von Zersiedelung und Entverdichtung der Städte sowie Entwicklung in Richtung Stadt der kurzen Wege.

The city of Ebreichsdorf is a fast growing municipality in the metropolitan region of Vienna, Lower Austria and Burgenland. Especially the southern suburbs of Vienna such as the region surrounding Ebreichsdorf are gaining from the growth of the Austrian Capital City Vienna. The expansion of the railroad track of "Pottendorfer Linie" to a double track railroad and the thereby even better connexion from Ebreichsdorf to Vienna will strengthen its growth process even more. A new regional mobility hub is planned to be built, located on a greenfield site, between the city districts Ebreichsdorf and Unterwaltersdorf. The existing railway track is going to be abandoned. In spatial planning terms, its leading goal is to locate future growth in the area of the new train station. Unfortunately, Austrian planning practice tends to adopt reactive behaviour in the context of infrastructure and settlement development. Thus, simultaneous planning of high-level-infrastructure and surrounding station area is mostly missed. Especially small and medium-sized cities are often overwhelmed by this task. The results of this uncoordinated approach vary from non-development of suitable land to uncoordinated urban sprawl around the stations. Furthermore, only reactive actions can be taken to contain negative consequences and to enable an orderly, soil-saving settlement development. Therefore, in February 2016 the Smart City Ebreichsdorf project (SMCE) started as an exploratory study funded by the Klima- und Energiefonds (KLIEN "climate and energy fund") with a duration of one year. The research focus was on creating a proactive planning community together with citizens by acting on four thematic topics: planning and process; railway station; district; and energy and resources, to. As a result, four scenarios have been developed for Ebreichsdorf including necessary dimensions of action. Criteria for an innovative implementation were defined and necessary actors for the continuing project were involved at an early stage of the development process. The Smart City concept obtains incresasing importance in the course of urban and regional development. Thereby, new technologies are used to create a sustainable environment and economy in order to ensure quality of life for further generations. Particular measures are: minimizing soil sealing, adopting technologies for future mobility, preventing urban sprawl, de-densification, as well as creating cities of short distances. The participation and awareness of the citizens are of fundamental importance. Using the example of the test bed Ebreichsdorf, the main aim of the SMCE project is to demonstrate proactive city development with an overall systemic, interdisciplinary approach to an area, and involving the population and the relevant stakeholders of the political, administrative and private sectors. This paper examines how this proactive planning-process of Smart City Ebreichsdorf is working. It shows the development process in the exploratory project and its results and explains the integrated dimensions of action. Building on this, it presents the current project and new planning approaches, e.g. to avoid soil sealing. With a focus on Ebreichsdorf, this paper demonstrates how such a proactive planning process can be used for a smart urban and regional development.
Keywords: Stadtregion; Stadtentwicklungsplanung; Regionalplanung; Smart City; Verkehrsplanung; Eisenbahnstrecke; Bahnhof; Partizipation; Kooperative Planung; Bewohnerbeteiligung; Forschungsprojekt